2009
DOI: 10.1093/jjco/hyp141
|View full text |Cite
|
Sign up to set email alerts
|

Massive Hematuria from the Bilateral Upper Urinary Tract in a Patient Treated for Advanced Lung Cancer with Gefitinib

Abstract: We report a case of gefitinib-induced bilateral upper urinary tract bleeding in an 82-year-old woman administered the drug daily for advanced non-small cell adenocarcinoma of the lung (T4N3M0). Hematuria is an uncommon adverse effect of gefitinib, and in most cases, the bleeding site is unknown. On the 44th day of oral gefitinib administration, the patient noted asymptomatic macroscopic bloody urine. Cystoscopy revealed bleeding from the bilateral ureteric orifices without hemorrhagic inflammation of the bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In our patient immediate discontinuation of gefitinib and treatment of the hemorrhagic cystitis by fluid and urine alkalizing agents prevented the occurrence of more severe kidney damage and led to the disappearance of the adverse effects, while the patient still showed a remarkable response to therapy 11 .…”
Section: E4mentioning
confidence: 62%
“…In our patient immediate discontinuation of gefitinib and treatment of the hemorrhagic cystitis by fluid and urine alkalizing agents prevented the occurrence of more severe kidney damage and led to the disappearance of the adverse effects, while the patient still showed a remarkable response to therapy 11 .…”
Section: E4mentioning
confidence: 62%
“…Renal dysfunction was occurred in about 1 %. Other side effects were post-renal acute renal failure due to urinary bleeding or retroperitoneal fibrosis [19]. A case of acute renal failure due to thrombotic thrombocytopenic purpura/hemolytic uremic syndrome was also reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies of gefitinib have demonstrated a urinary recovery of only <0.5%, indicating that the urinary system is only a minor route of excretion (4). Despite being generally well-tolerated, a small subset of patients have reported uncommon gefitinib-induced adverse reactions affecting the urinary system, including acute renal failure (10), hematuria (12), hemorrhagic cystitis (11,13), and inflammatory contracted bladder (11). In vitro studies have demonstrated that EGFR signaling is involved in the proliferation of urothelial cells, and gefitinib can inhibit the growth of normal urothelial cells and urothelial carcinoma cell lines (16).…”
Section: G E F I T I N I B I S E F F E C T I V E I N P a T I E N T S ...mentioning
confidence: 99%
“…At the standard recommended dose, gefitinib has a tolerable safety profile (4)(5)(6), with reported adverse reactions primarily involving the gastrointestinal system (i.e., diarrhea, nausea, vomiting), skin (i.e., rash, acne, dry skin), and liver [i.e., elevated alanine aminotransferase (ALT) and aspartate transaminase (AST)] (2,5,7). However, uncommon adverse reactions have been reported, including hematuria and hemorrhagic cystitis (8)(9)(10)(11)(12)(13)(14). Clinicians should pay more attention on monitoring for urinary symptoms and hematuria.…”
Section: Introductionmentioning
confidence: 99%